Positivity in algebraic geometry II positivity for vector bundles, and multiplier ideals - Lazarsfeld Robert (Berlin Springer-Verlag, 2004)
This two volume work on Positivity in Algebraic Geometry contains a contemporary account of a body of work in complex algebraic geometry loosely centered around the theme of positivity. Topics in Volume I include ample line bundles and linear series
Keywords: Algebraic geometry